Respuesta :
x is 1.
first, you distribute the 5 into the parentheses.
5(2x-8)+15=-15 becomes 10x-40+15=-15
then you calculate the sum
10x-40+15=-15 becomes 10x-25=-15
after that you move the constant to the right of the equal sign and change the sign (ex negative becomes positive number)
10x-25=-15 becomes 10x=-15+25
next, you add the constants
10x=-15+25 becomes 10x=10
lastly, you divide the numbers.
10x=10 becomes 1
so x=1
first, you distribute the 5 into the parentheses.
5(2x-8)+15=-15 becomes 10x-40+15=-15
then you calculate the sum
10x-40+15=-15 becomes 10x-25=-15
after that you move the constant to the right of the equal sign and change the sign (ex negative becomes positive number)
10x-25=-15 becomes 10x=-15+25
next, you add the constants
10x=-15+25 becomes 10x=10
lastly, you divide the numbers.
10x=10 becomes 1
so x=1
Original Equation.
5(2x - 8) + 15 = -15
First do what is in the parenthesis.
2 x 1 = 2
2 - 8 = -6
5(-6) + 15 = -15
Multiply 5 x -6 to get -30
-30 + 15 = -15
add 15 + -30 to get -15
-15
x = 1
Hope This Helps!
Can I get Brainliest?